Komunikasi Multikultural Badan Sosial Lintas Agama (BASOLIA) dalam Merajut Toleransi di Era Society 5.0 - Rahmawati, Yulia; Hariyati, Farida (Jurnal Komunikasi Universitas Garut: Hasil Pemikiran dan Penelitian, 2024)
Indonesia has the motto Bhinneka Tunggal Ika which reflects being a multicultural nation with many tribes, languages, religions and cultures. This diversity brings harmony through multicultural communication. Globalization is currently seen as a big wave that brings impacts and changes in various aspects of life. Including changes in life from the industrial era 4.0 to the era of society 5.0. Entering the era of society 5.0, where people's activities implement technology with a focus on humanity, it is a part of technology to be part of the development of a multicultural society in harmony.  Multicultural communication is part of harmony, because the process of interaction and communication involves cultural concepts. The Interfaith Social Agency (BASOLIA) is an organization that operates in the social and humanitarian fields interreligiously in the social and humanitarian fields. However, BASOLIA actively participates in maintaining religious harmony in the city of Bogor. The focus of this research is on the analysis of multicultural communication at the Bogor City Interfaith Social Agency (BASOLIA). The aim of this research is to analyze the multicultural communication of the Interfaith Social Agency (BASOLIA) in fostering tolerance in the era of society 5.0. This research uses a descriptive qualitative approach using the case method. Data collection was carried out by observation, interviews and literature review, then analyzed using the data reduction, data presentation and data verification stages. The results of this research show that BASOLIA in its activities cannot be separated from multicultural communication. The meeting room becomes a symbolic interaction with tolerance dialogue, where by building regular discussions or dialogue, both formal and informal, it becomes part of multicultural communication in program activities carried out by BASOLIA in maintaining multiculturalism in the city of Bogor.